New Eco-friendly UV-spectroscopic Methods for Simultaneous Assessment of Dapagliflozin, Saxagliptin and Metformin in Ternary Mixture - Sen, Dhanya B; Jatu, Sohil; Maheshwari, Rajesh A; Zanwar, Aarti Sachin; Velmurugan, Ramaswamy; Sen, Ashim Kumar (Indian Journal of Pharmaceutical Education and Research, 2023)
Background and Aim: Qternmet XR® consisting of dapagliflozin (10 mg), saxagliptin (5 mg), and metformin hydrochloride (1000 mg), is a fixed-dose combination (tablets) that improves glycemic control in individuals with diabetes mellitus (type 2). The projected work presents four spectrophotometric methods that are eco-friendly, quick, effortless, accurate and reproducible for the concurrent assessment of the ternary mixture. Materials and Methods: The 1st approach works on the notion of unravelling pre-existing equations (simultaneous) by measuring absorbance at 223, 212 and 232.6 nm for dapagliflozin, saxagliptin and metformin hydrochloride, sequentially. The second method namely ratio difference spectroscopy works by evaluating the variation in amplitude at two dissimilar wavelengths in the ratio spectra. Whereas the derivative ratio spectrum zero-crossing approach (third approach) relied on the utilization of the derivative ratio signals at zero-crossing locations. The fourth approach is the double divisor-ratio spectra derivative approach in which the first derivative of ratio spectrum was acquired and the concentrations of all 3 drugs in their combination were quantified. Results and Discussion: All the three drugs exhibited excellent linear correlation in the concentration series of 2-10 µg/mL for simultaneous equation method and 0.5-10 µg/mL for all the other methods with an exceptional correlation coefficient value. Furthermore, the projected approaches were authenticated in line with ICH strategies and which displayed suitable precision, accuracy and sensitivity. Conclusion: The developed spectrophotometric approaches when compared to other analytical procedures are regarded to be more cost-effective because they do not require expensive solvents or sophisticated instruments. Therefore, the projected methods could be effectively employed for the concurrent assessment of dapagliflozin, saxagliptin and metformin hydrochloride in ternary mixture.
Keywords: Dapagliflozin; Saxagliptin; Metformin; Simultaneous Equation Method; Ratio Difference Spectroscopic approach; Derivative Ratio Spectrum-Zero crossing approach; Double Divisor Ratio Spectra Derivative approach; Ternary mixture